Comprehensive analyses of the citrus WRKY gene family involved in the metabolism of fruit sugars and organic acids - Zhang, Mingfei; Lu, Wen; Yang, Xinxia; Li, Qin; Lin, Xingyu; Liu, Kexin; Yin, Chunmei; Xiong, Bo; Liao, Ling; Sun, Guochao; He, Siya; He, Jiaxian; et al. (Frontiers in Plant Science, 2023)
The sugar and organic acid are the main factors determining the flavor of citrus fruit. The WRKY transcription factor family plays a vital role in plant growth and development. However, there are still few studies about the regulation of citrus WRKY transcription factors (CsWRKYs) on sugar and organic acid in citrus fruit. In this work, a genome-wide analysis of CsWRKYs was carried out in citrus genome, and a total of 81 CsWRKYs were identified which contained conserved WRKY motifs. Cis-regulatory elements analysis revealed that Most of the CsWRKYs promoters contained several kinds of hormone-responsive and abiotic responsive cis-elements. Further gene expression analysis and fruit quality determination showed that multiple CsWRKYs were closely linked to fruit sugar and organic acid with the development of citrus fruit. Notably, transcriptome co-expression network analysis further indicated that three CsWRKYs, namely CsWRKY3, CsWRKY47 and CsWRKY46, co-expressed with multiple genes involved in various pathways, such as Pyruvate metabolism and Citrate cycle. These CsWRKYs may participate in the metabolism of fruit sugar and organic acid by regulating carbohydrate metabolism genes in citrus fruit. These findings provide comprehensive knowledge of the CsWRKY family on the regulation of fruit quality.